Participatory Institutions and People’s Practices in India: An analysis of Decentralisation experiences in Kerala State - K Rajesh (2011)
Institutions orient people towards a common goal. Institutions have a pertinent role in collective action. Participatory institutions have the potential to vitalize democracy by providing a pro active role to the citizens in decision making, planning and implementation of activities. In fact the performance of the institutions depends upon the practices of the people affiliated to them. The practices of the people are influenced by the field in which they are situated, and their habitus. Ultimately field (It is an objective historical relation between the positions in each realm of the society) and habitus ( It is the way in which field enters in to an individual) are the decisive factors in people’s practices. Kerala’s decentralization experiments since the inception of the People’s Planning Campaign in 1996 have given more emphasis to participatory institutions. PPC viewed participatory institutions as forums for mobilizing different groups of people towards grassroots level democracy. This paper analyses the dynamics of institutions created by PPC in Kerala in light of their twelve years of functioning. The Paper also considers various factors that might have affected the functioning of institutions through a detailed analysis of Kerala’s political, economic, cultural and religious fields.